Thermonuclear explosions of rapidly differentially rotating white dwarfs: candidates for superluminous type Ia supernovae? - Fink, Mario; Kromer, Markus; Röpke, Friedrich; Pakmor, Rüdiger (Astronomy and astrophysics, 2018)
The observed sub-class of “superluminous” Type Ia supernovae lacks a convincing theoretical explanation. If the emission of such objects were powered exclusively by radioactive decay of 56Ni formed in the explosion, a progenitor mass close to or even above the Chandrasekhar limit for a non-rotating white dwarf star would be required. Masses significantly exceeding this limit can be supported by differential rotation. We, therefore, explore explosions and predict observables for various scenarios resulting from differentially rotating carbon-oxygen white dwarfs close to their respective limit of stability. Specifically, we have investigated a prompt detonation model, detonations following an initial deflagration phase (“delayed detonation” models), and a pure deflagration model. In postprocessing steps, we performed nucleosynthesis and three-dimensional radiative transfer calculations, that allow us, for the first time, to consistently derive synthetic observables from our models. We find that all explosion scenarios involving detonations produce very bright events. The observables predicted for them, however, are inconsistent with any known subclass of Type Ia supernovae. Pure deflagrations resemble 2002cx-like supernovae and may contribute to this class. We discuss implications of our findings for the explosion mechanism and for the existence of differentially rotating white dwarfs as supernova progenitors.